Tìm x, biết: x 4 = 7
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
x.8+56+x.4-28=x.3+9+x+4*(1-3)
=>12x+(56-28)=(3x+x)+9+4*(-2)
=>12x+28=4x+9-8=4x+1
=>12x-4x=1-28
8x=-27
x=-27/8
![](https://rs.olm.vn/images/avt/0.png?1311)
( 3x - 24 ) . 73 = 2 . 74
3x - 16 = 2 . 74 : 73 = 14
3x = 14 + 16 = 30
x = 10
\(\left(3\times x-2^4\right)\times7^3=2\times7^4\)
\(\left(3\times x-2^4\right)\div2=7^4\div7^3\)
\(\left(3\times x-16\right)\div2=7\)
\(3\times x-16=7\times2\)
\(3\times x-16=14\)
\(3\times x=14+16\)
\(3\times x=30\)
\(x=30\div3\)
\(x=10\)
![](https://rs.olm.vn/images/avt/0.png?1311)
x+4/7+y = 4/7
=> (x + 4)7 = 4(y + 7)
=> 7x + 28 = 28 + 4y
=> 7x = 4y
=> x/4 = y/7
=> x + y/4 + 7 = x/4 = y/7 mà x + y = 77
=> 77/11 = x/4 = y/7
=> 7 = x/4 = y/7
=> x = 28; y = 49
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Ta có:
1; 4; 7;...; 100 có (100 - 1) : 3 + 1 = 34 (số)
1 + 4 + 7+ ... + 100 = (100 + 1) × 34 : 2
= 101 × 17
(1 + 4 + 7 + ... + 100) : a = 17
101 × 17 : a = 17
a = 101 × 17 : 17
a = 100
b) (X - 1/2) × 5/3 = 7/4 - 1/2
(X - 1/2) × 5/3 = 5/4
X - 1/2 = 5/4 : 5/3
X - 1/2 = 3/4
X = 3/4 + 1/2
X = 5/4
a) (1 + 4 + 7 +...+ 100) : a = 17
1717 : a = 17
a = 101
b) \(\left(x-\dfrac{1}{2}\right)\times\dfrac{5}{3}=\dfrac{7}{4}-\dfrac{1}{2}\)
\(\left(x-\dfrac{1}{2}\right)\times\dfrac{5}{3}=\dfrac{10}{8}\)
\(\left(x-\dfrac{1}{2}\right)=\dfrac{10}{8}\div\dfrac{5}{3}\)
\(\left(x-\dfrac{1}{2}\right)=\dfrac{10}{8}\times\dfrac{3}{5}\)
\(\left(x-\dfrac{1}{2}\right)=\dfrac{3}{4}\)
\(x-\dfrac{1}{2}=\dfrac{3}{4}\)
\(x=\dfrac{3}{4}+\dfrac{1}{2}\)
\(x=\dfrac{5}{4}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x+y=55\Rightarrow x=55-y\\ \Leftrightarrow\dfrac{4+55-y}{7+y}=\dfrac{4}{7}\\ \Leftrightarrow28+385-7y=28+4y\\ \Rightarrow y=35\\ \Rightarrow x=55-35=20\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{x+4}{4}=\dfrac{y+7}{7}\)Theo tc dãy tỉ số bằng nhau
\(\dfrac{x+4}{4}=\dfrac{y+7}{7}=\dfrac{x+y+4+7}{11}=\dfrac{33}{11}=3\Leftrightarrow x=8;y=14\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{4}{5}.x=\dfrac{4}{7}\)
\(\Leftrightarrow x=\dfrac{4}{7}\div\dfrac{4}{5}\)
\(\Leftrightarrow x=\dfrac{4}{7}\times\dfrac{5}{4}\)
\(\Leftrightarrow x=\dfrac{5}{7}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
(x-1/2).5/3=7/4-1/2
(x-1/2).5/3=5/4
x-1/2=5/4:5/3
x=3/4+1/2
x=5/4
(x-4/3).7/4=5-7/6
(x+4/3).7/4=23/6
x+4/3=23/6:7/4
x+4/3=46/21
x=46/21-4/3
x=6/7
Ta có: x 4 = 7 ⇔ x 2 2 = 7
⇔ x 2 = 7 ⇔ x 2 = 7
Vậy x = 7 và x = - 7